A structural biology perspective on bioactive small molecules and their plant targets. - Kumari, S; van der Hoorn, R (2011)
Structural biology efforts in recent years have generated numerous co-crystal structures of bioactive small molecules interacting with their plant targets. These studies include the targets of various phytohormones, pathogen-derived effectors, herbicides and other bioactive compounds. Here we discuss that this collection of structures contains excellent examples of nine collective observations: molecular glues, allostery, inhibitors, molecular mimicry, promiscuous binding sites, unexpected electron densities, natural selection at atomic resolution, and applications in structure-guided mutagenesis and small molecule design.